Cooperação Transfronteiriça para o Desenvolvimento Regional - Eliane Salete Filippim (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
This study addresses the issue of cooperation in the area along the border and assumes that the local territory constitutes an arena for the discussion and consolidation of decentralized and creative solutions to common problems, both for the management of public policies and for shared processes of sustainable development. The main objective was to describe and analyze the cooperation that exists in the border area between the municipalities of Dionysus Cerqueira (SC / BR) and Bernardo de Irigoyen (Misiones / AR). A qualitative, descriptive and exploratory research was conducted, using a case study strategy that included the analysis of documents, semi-structured interviews and nonsystematic observation of the study site. The results demonstrate that the cooperation between the border towns has enabled a sharing of common problems (Argentina/Brazil), fostered the deve - lopment and implementation of joint public policies, and created opportunities for the improvement of the design of the border area governance system.